APPLICATION OF GIS SYSTEMS DURING THE LAND MANAGEMENT OF CITIES OF UKRAINE - , К. А. (Municipal economy of cities. Series: «Economy science», 2016)
The article is to determine trends and features of GIS in the land cities of Ukraine. The study found that the processes affecting land bridge indicators that characterize urban development. As part of the project proposed geo urban indicators reflect the territorial, quantitative spatial characteristics of the city. Directions GIS development projects implemented in the land bridge. It was established that the land bridge processes affecting intensity residential development. Using GIS tools developed appropriate project presented to determine the rate, which is rated one of the leading companies for the district. Kharkov. In the article the features of application of geographic information systems in the land of cities of Ukraine. The developed GIS project on assessment of urban development. Kharkov. A Geoinformation tools to determine the intensity of the development areas that affect the processes of land bridge. Keywords: Geographic information system, land administration, building development, intensity build of land.